SCAI Expert Consensus Statement on the Management of Patients With STEMI Referred for Primary PCI - Jacqueline E. Tamis-Holland, MD, FSCAI (Chair); J. Dawn Abbott, MD, FSCAI; Karim Al-Azizi, MD, FSCAI; Nitin Barman, MD; Anna E. Bortnick, MD, PhD, MSc, FSCAI; Mauricio G. Cohen, MD, FSCAI; Payam Dehghani, MD, FSCAI; Timothy D. Henry, MD, MSCAI; Faisal Latif, MD, FSCAI; Mohammad Madjid, MD, FSCAI; Celina M. Yong, MD, MBA, MSc, FSCAI; Yader Sandoval, MD, FSCAI (Co-Chair) (Journal of the Society for Cardiovascular Angiography & Interventions)
ST-elevation myocardial infarction (STEMI) remains a leading cause of morbidity and mortality in the United States. Timely reperfusion with primary percutaneous coronary intervention is associated with improved outcomes. The Society for Cardiovascular Angiography & Interventions puts forth this expert consensus document regarding best practices for cardiac catheterization laboratory team readiness, arterial access with an algorithm to help determine proper arterial access in STEMI, and diagnostic angiography. This consensus statement highlights the strengths and limitations of various diagnostic and therapeutic interventions to access and treat a patient with STEMI in the catheterization laboratory, reviews different options to manage large thrombus burden during STEMI, and reviews the management of STEMI across the spectrum of various anatomical and clinical circumstances.